2014
DOI: 10.1098/rspb.2013.2934
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of signal–reward correlations in bee- and hummingbird-pollinated species ofSalvia

Abstract: Within-individual variation in floral advertising and reward traits is a feature experienced by pollinators that visit different flowers of the same plant. Pollinators can use advertising traits to gather information about the quality and amount of rewards, leading to the evolution of signal-reward correlations. As long as plants differ in the reliability of their signals and pollinators base their foraging decisions on this information, natural selection should act on within-individual correlations between si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Hence, quantitative measures of the magnitude of individual phenotypic integration of functional traits (Wilson & Nussey, 2010), coupled with estimations of plant fitness, offer an opportunity to assess its adaptive value under natural conditions. Until now, most efforts testing the adaptive value of covariance in plants have been conducted only on flower morphology as an adaptation to optimise pollination (Ordano et al, 2008;Ben ıtez-Vieyra et al, 2014;L azaro & Santamar ıa, 2016), whereas very limited information is available for leaf traits (Bontemps et al, 2017). The main goal of the present study was to experimentally test whether plant fitness is related to the degree of covariation among particular sets of leaf functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, quantitative measures of the magnitude of individual phenotypic integration of functional traits (Wilson & Nussey, 2010), coupled with estimations of plant fitness, offer an opportunity to assess its adaptive value under natural conditions. Until now, most efforts testing the adaptive value of covariance in plants have been conducted only on flower morphology as an adaptation to optimise pollination (Ordano et al, 2008;Ben ıtez-Vieyra et al, 2014;L azaro & Santamar ıa, 2016), whereas very limited information is available for leaf traits (Bontemps et al, 2017). The main goal of the present study was to experimentally test whether plant fitness is related to the degree of covariation among particular sets of leaf functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…Corolla tube length and width, corolla lower lip length and width, and corolla upper lip length and height were measured for each flower (Figure ). We focused on corolla traits, given that they belong to a single ontogenetic unit and because pollinator behaviour strongly suggests that different corolla parts have different functions in bee‐ and hummingbird‐pollinated species (Benitez‐Vieyra et al., ). Data were log‐transformed to linearize the relationships among floral traits due to allometric growth (Huxley, ) and to allow variance and covariance comparisons among traits and species (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Berg's hypothesis relies on the expectation that the morphological matching between flowers and pollinators is essential to ensure efficient pollen delivery and reception. Although there has been increasing interest in the functional role of variances and covariances among functional floral traits (Armbruster, Pelabon, Bolstad, & Hansen, 2014;Benitez-Vieyra, Fornoni, Perez-Alquicira, Boege, & Dominguez, 2014;Herrera, 2009;Murren, 2012;Ordano, Fornoni, Boege, & Domínguez, 2008;Pérez-Barrales, Arroyo, & Scott Armbruster, 2007), we are still far from deciphering how they evolve during evolutionary transitions among pollination syndromes (Armbruster, Di Stilio, Tuxill, Flores, & Velázquez Runk, 1999;Armbruster et al, 2014;Fornoni, Ordano, Pérez-Ishiwara, Boege, & Domínguez, 2016). A recent work proposed that studying the coordinated action of multiple traits represents an unexplored opportunity to better understand adaptive transitions during evolution (Fenster, Reynolds, Williams, Makowsky, & Dudash, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…) and was suggested as the mechanism causing adaptive divergence of honest signals among Salvia species with different pollinators (Benitez‐Vieyra et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Such 'indirect' honest signalling could be maintained by a constraint (Juenger et al 2000;Conner 2002) as well as pollinator-mediated selection (Stanton & Young 1994). In Turnera ulmifolia positive selection on signal accuracy, namely the correlation of flower size and nectar amount, has been found (Benitez-Vieyra et al 2010) and was suggested as the mechanism causing adaptive divergence of honest signals among Salvia species with different pollinators (Benitez-Vieyra et al 2014).…”
Section: Introductionmentioning
confidence: 99%